Effectiveness of the progestin-only pill for migraine treatment in women: A systematic review and meta-analysis. (April 2018) - Warhurst, Samantha; Rofe, Christopher J; Brew, Bruce J; Bateson, Deborah; McGeechan, Kevin; Merki-Feld, Gabriele S; Garrick, Raymond; Tomlinson, Susan E
Background: Migraine is highly prevalent in women (18%). Peak morbidity affects their most productive years, coinciding with peak fertility. Hormonal contraception is often tailored for migraine prevention. Estrogen-containing contraceptives may be contraindicated in women experiencing migraine with aura due to the risk of vascular events. While improvements in migraine with a progestin-only pill (POP), which inhibits ovulation are documented, the strength and quality of evidence has not been formally evaluated. Objectives: To determine the effectiveness of progestin-only contraceptives for migraine treatment by systematic review and meta-analysis. Data sources and selection: MEDLINE, EMBASE and Cochrane Libraries were searched (1980 to September 2016) for studies on progestin-only treatments for migraine. Studies in English on >4 non-menopausal women aged 18–50 with migraine diagnosed by formal criteria were included. Data extraction and analysis: Data were quality-assessed using the GRADE system. A random effects model was used for pooled analyses. Results: Pooled analyses of four studies demonstrated that desogestrel 75 mcg/day, POP significantly but modestly reduced the number of migraine attacks and migraine days. Reduced intensity and duration, reduced analgesic and triptan use were observed, along with improved headache-related quality of life. GRADE analysis indicated evidence was low to very low for each outcome measure. Adverse effects resulted in treatment cessation for <10% of participants. Two studies compared desogestrel POP to a combined oral contraceptive, demonstrating similar migraine outcomes for both treatments. Conclusions: The desogestrel POP shows promise in improving migraine in women. Current evidence is observational and based on small samples of women using only one oral progestin-only formulation. Further randomized trials on additional progestin-only contraceptives are required to confirm their role in migraine management.